Static and dynamic modeling of organic thin-film transistors for circuit design. (July 2016) - Jiang, Li; EI-Masry, Ezz; Hill, Ian G.
Abstract: A new static and dynamic model for organic thin-film transistors (OTFTs) is proposed. The model incorporates a gate-voltage dependent mobility, drain/source contact series resistance, threshold voltage variation with bias and channel length, and drain induced barrier lowering effect. The model also takes into account all the operating regions and includes static and dynamic characteristics of OTFTs. It is developed using a physical basis where the model's parameters can easily be extracted from the experiment data. The model is suitable for computer aided design applications and has been verified by device simulations and measurements from both p-type and n-type OTFTs.